Polyenylcyclopropane carboxylic esters with high insecticidal activity. Issue 5 (3rd July 2014) - Ferroni, Claudia; Bassetti, Lucio; Borzatta, Valerio; Capparella, Elisa; Gobbi, Carlotta; Guerrini, Alberto; Varchi, Greta
Abstract BACKGROUND Pyrethroids are synthetic derivatives of naturally occurring pyrethrum. These molecules are widely used in agriculture for ant, fly and mosquito control and for lawn and garden care. Pyrethroids are the optically active esters of 2, 2‐dimethyl‐3‐(2‐methylpropenyl)‐cyclopropane carboxylic acid, also known as chrysanthemic acid. However, their intense use has resulted in the development of resistance in many insect species. Herein, specific structural modifications of the pyrethroid scaffold and their effect on insecticidal activity, especially on resistant pests strains, are reported. RESULTS The exposure to (1R)‐trans‐(E/Z)‐2, 3, 5, 6‐tetrafluorobenzyl‐3‐(buta‐1, 3‐dienyl)‐2, 2‐dimethyl cyclopropanecarboxylate and its diastereomers produced 100% mortality in yellow fever mosquitoes (Aedes aegypti), house mosquitoes (Culex quinquefasciatus) and houseflies (Musca domestica). Moreover, this compound provided complete knockdown within 15 min of exposure against cockroaches (Blattella germanica) and maintained an excellent knockdown activity at 10 days after treatment. CONCLUSION Novel pyrethroid derivatives obtained from 2, 2‐dimethyl‐3‐(2‐methylpropenyl)‐cyclopropanecarboxylic acid are described. These derivatives display high insecticidal activity, a wide spectrum of action and no toxicity towards mammalians. The proposed synthetic procedures are highly efficient and inexpensive, and therefore suitable for industrial scale‐up. © 2014 Society of Chemical Industry